2012
DOI: 10.1007/s12325-012-0072-2
|View full text |Cite
|
Sign up to set email alerts
|

Epoetin Biosimilars in Europe: Five Years On

Abstract: Biosimilars have been developed for several biologic therapeutic agents, including erythropoiesis-stimulating agents (ESAs).However, biosimilars cannot be assumed to be completely identical to the reference product, nor can two different biosimilars of the same reference product be considered equivalent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“…It is interesting to note that there were no significant differences between the originator and biosimilar groups with regard to clinical characteristics at baseline, except that the patients undergoing therapy with biosimilar products were older than those who started with reference product. Moreover, as observed in other studies,25,33,34 this study showed no significant differences between the two groups in ΔHb levels 2 months after the initiation of treatment.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It is interesting to note that there were no significant differences between the originator and biosimilar groups with regard to clinical characteristics at baseline, except that the patients undergoing therapy with biosimilar products were older than those who started with reference product. Moreover, as observed in other studies,25,33,34 this study showed no significant differences between the two groups in ΔHb levels 2 months after the initiation of treatment.…”
Section: Discussionsupporting
confidence: 87%
“…Since the expiration of patent protection, a number of novel biosimilar epoetins have been approved on the world market 23,25. Biosimilar medicines have significant potential to offer cost savings to health care providers, but the global value of a biosimilar is not determined entirely by its pricing 26.…”
Section: Discussionmentioning
confidence: 99%
“…It has the same amino acid sequence as epoetin alfa (22,23). In a PK study comparing HX575 with branded epoetin alfa enrolling 80 healthy men, the pharmacodynamic (PD) results for the two agents were similar.…”
Section: Hx575 (Binocrit)mentioning
confidence: 99%
“…Immunological reactions to a biologic drug are amongst the most important adverse reactions that are possible. While reactions can be simply developing antibodies with no clinical consequences, antibodies themselves can result in systemic immune reactions, autoimmunity to endogenous proteins or the undermining of therapeutic efficacy through antibodies targeting endogenous proteins [6]. Nephrologists are well aware of PRCA that occurred as a result of a formulation change of Eprex® introduced years after original marketing, despite the comparability exercises performed.…”
Section: Reviewmentioning
confidence: 99%